2017
DOI: 10.17993/ecoorgycso.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Urban Water Supply in Mexico

Abstract: Quedan todos los derechos reservados. Esta publicación no puede ser reproducida, distribuida, comunicada públicamente o utilizada, total o parcialmente, sin previa autorización.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As stated in various previous studies, the level of arsenic in drinking water samples in Chihuahua State had been above the WHO maximum permissible limits and the current Mexican standard level (10 μg/L) [51][52][53][54]. However, although no recent study was found to express the arsenic level of drinking water in Nuevo León, it had been reported as much lower than the Chihuahua rate and below WHO and Mexican standard maximum limits in 2004 [54].…”
Section: Discussionmentioning
confidence: 96%
“…As stated in various previous studies, the level of arsenic in drinking water samples in Chihuahua State had been above the WHO maximum permissible limits and the current Mexican standard level (10 μg/L) [51][52][53][54]. However, although no recent study was found to express the arsenic level of drinking water in Nuevo León, it had been reported as much lower than the Chihuahua rate and below WHO and Mexican standard maximum limits in 2004 [54].…”
Section: Discussionmentioning
confidence: 96%
“…The perpetual shortages and mal-disposition of available water reservoirs is in part a product of the country’s long-standing bureaucratic and complex management infelicities. Put another way, Mexico has not yet succeeded in creating an administrative framework that adequately meets the water needs of all its citizens (Silva Rodríguez de San Miguel, 2017). There have also been well-publicized instances of corruption and abuse, with high-ranking government officials receiving copious amounts of water piped directly to their residences, while impoverished communities receive barely any water at all (Herrera, 2017).…”
Section: Introductionmentioning
confidence: 99%